Crowd cash and the city: understanding the (re)emergence of the crowd as a financial ‘actor’ and its reimagining of urban development futures - Daniels, Joseph Allen (2022)
Crowds have (re)emerged as a cultural economic phenomenon over the past decade, often eliciting fervent financial fantasies of democratic distribution and public participation. New collective claims are being made over circuits of value and money. This is particularly evident in the rapid proliferation of the crowdfunding economy. This ‘new’ economy has become so pronounced that urban governments are now turning to ‘crowds’ to improve public finance. Latest reports have indicated 45 (12 percent) of the United Kingdom’s councils are attempting to ‘crowdfund themselves out of crisis’ and that crowdfunding will become the de-facto community development mechanism for U.K. councils. How do we understand this ‘crowdfunded urbanism’? This research draws attention to the ‘crowd’ as is it rendered into a financial market actor through three accountings of this phenomenon. First, it seeks to provide a genealogical account of ‘crowds’ in the context of finance, with an eye towards critique of dominant understandings of ‘wise crowds’. Second, it provides an empirical study of the marketization of urban crowdfunding, tracing the assemblage of actors, technologies, and discourses that are deployed to ‘make’ urban crowdfunding markets (particularly in the U.K.). This draws in a new sensibility towards the collective within study of financial markets and their incursions into urban life. And finally, it attempts to assess the implications of urban crowdfunding as a technology of urban financial governance. Is this a potentially proliferative space of the diverse economy or appropriated by existing financializing capitalist economy? In other words, this study of crowdfunding attempts to elucidate the intersecting processes of market making and the emergent ‘platform economy’. It illustrates how dramatically ‘crowd thinking’ has shifted. It is reliant on dissociations with irrationality and with cities in order to provide the ‘solution’ for the present. And yet, ‘classical’ crowd thinking offers a new entry point into the critique of markets. It reveals the iterative interaction of ‘crowd thinking’ and ‘the crowd’ in practice. And finally, argues that while ‘the crowd’ might open up political space for thinking the world differently, it is too often contained within ‘platform capitalism’.